Affirmative action in procurement for open standards and FLOSS (Journal of Open Law, Technology & Society, 2011)
The Dutch action plan Netherlands Open in Connection intends to give a direction for public sector buyers to adopt a positive policy and strategy towards open standards and Free and open source software. This policy seems to indicate a preferred position on open source products, however it actually gives no guarantee that providers of free and open source software will get the opportunity to make an offer. First there should be a so called 'level playing field' for the suppliers. In an empirical study carried out between January and June 2010 the following question is answered: does European procurement law give a fair chance to vendors of FLOSS software? This study shows that despite of the desired affirmative action for open source products, in almost half (47.5%) of the tenders there is still a preference for closed source vendors or products. This preference inevitably results in not giving vendors of FLOSS software a fair chance to win the bid.